The impact of lymphoma and treatment on male fertility. Issue 6 (December 2010) - Eghbali, Houchingue; Papaxanthos-Roche, Aline
Most patients with Hodgkin's or non-Hodgkin's lymphomas will be cured by modern chemotherapy and/or radiotherapy. Although some patients, especially those with Hodgkin's lymphoma, already have semen alterations related to their disease before treatment, sperm damage is mainly caused by anti-cancer treatments. Alkylating and similar drugs and radiation therapy are the most aggressive agents on male gonadal functions. Sperm damage is dependent on drug dose and individual sensitivity, and the recovery is unpredictable. Current approaches to fertility management include the exclusion of gonadotoxic agents whenever possible, in particular among children and preadolescent boys, and systematic sperm banking for all male patients, especially among adolescent patients and even in cases of poor sperm quality. New techniques of in vitro fertilization allow procreation even with poor sperm quality.